Inflammatory Myofibroblastic Tumor of the Kidney and Bilateral Lung Nodules in a Child Mimicking Wilms Tumor With Lung Metastases. Issue 6 (August 2015) - Dogan, Mehmet S.; Doganay, Selim; Koc, Gonca; Gorkem, Sureyya B.; Unal, Ekrem; Ozturk, Figen; Coskun, Abdulhakim
<x xml:space="preserve">Abstract</x> Renal inflammatory myofibroblastic tumor (IMT) is an extremely rare lesion especially in children. This report describes a case of renal IMT accompanied by multiple lung nodules mimicking Wilms tumor with lung metastasis in a 3-year-old boy. To our knowledge, this is a unique case of IMT which has not been reported in the literature previously.